Biodegradation of 3,4-dichloroaniline in a fluidized bed bioreactor and a steady-state biofilm Kinetic model. - Livingston,AG (Biotechnol Bioeng, 1991)
Mixed culture of microorganisms immobilized onto Celite diatomaceous earth particles were used to degrade 3,4-dichloroaniline (34DCA) in a three-phase draft tube fluidized bed bioreactor. Biodegradation was confirmed as the dominant removal mechanism by measurements of the concomitant chloride ion evolution. Degradation efficiencies of 95% were obtained at a reactor retention time of 1.25 h. A mathematical model was used to describe the simultaneous diffusion and reaction of 34DCA and oxygen in the biofilms on the particles in the reactor. The parameters describing freely suspended cell growth on 34DCA were obtained in batch experiments. The model was found to describe the system well for three out of four steady states and to predict qualitatively the experimentally observed transition in the biofilm kinetics from 34DCA to oxygen limitation.